I have almost finished, but I'm stuck at one place. Please guide.
Here is what I did:
Q. (¬p v q) ∧ (p ∧ (p ∧ q)) ⇔ p ∧ q
(¬p v q) ∧ ((p ∧ p) ∧ q) using Associative Law
(¬p v q) ∧ (p ∧ q) using idempotent Law
?
How to remove (¬p v q)?
Use some basic laws to rewrite $(\neg p\lor q)\land(p\land q)$ as
$$\big((\neg p\lor q)\land q\big)\land p$$
and show that $(\neg p\lor q)\land q$ is equivalent to $q$. How you do this will depend on exactly what laws you have available. It’s immediate if you have the absorption laws. Alternatively, you may have basic propositions $T$ and $F$ (or $1$ and $0$, or $\top$ and $\bot$) such that $q$ is equivalent to $F\lor q$. Then you can use a distributive law to change $(\neg p\lor q)\land(F\lor q)$ to $(\neg p\land F)\lor q$ and thence to $F\lor q$ and finally $q$.